A CFD-applicable discrete combustion model for thermally large particles. (7th October 2011) - Jarvinen, Mika; Mueller, Christian; Hupa, Mikko; Fogelholm, Carl-Johan
The objective of this paper is to present a comprehensive new single-particle combustion model that can be used effectively in Computational Fluid Dynamics (CFD) applications. As a major difference from standard particle sub-models used in CFD software packages, the new model is suitable for simulating thermally large particles, which means that it considers the intra-particle temperature gradients and overlapping stages of drying, pyrolysis and char conversion. The model was validated by comparison with experiments and also with a more detailed model presented in our earlier work. Although the model was applied here for black liquor combustion, it is also suitable and can be used for other different applications, such as the combustion of biomass, coal or heavy fuel oil and metallurgical processes.